种耐高温核电站用电缆及其制造方法 (2018)
种耐高温核电站用电缆，其结构为：由多根铜或镀锡铜金属单丝绞合构成导体；导体外包裹绝缘层；绝缘层外包裹聚酰亚胺薄膜构成线芯；多根线芯绞合构成缆芯；缆芯外包裹护套；所述绝缘层外包裹聚酰亚胺薄膜，可保证电缆耐高温、耐辐射要求。种耐高温核电站用电缆制造方法，步骤包括：1)多根铜或镀锡铜金属单丝绞合构成导体；2)采用连续硫化设备、挤包方式把绝缘材料包裹在导体外；3)采用绕包方式把聚酰亚胺薄膜包裹在线芯外；4)采用绞合的方式构成缆芯；5)在缆芯外采用连续硫化方式挤包护套。采用本方法制得的电缆，能满足设计要求。 The structure of a high-temperature resistant cable for a nuclear power plant comprises conductors, wherein each conductor is formed by twisting a plurality of copper or tin plated copper metal single wires, an insulation layer wraps the conductor, a polyimide film wraps the insulation layer to form a wire core, a plurality of wire cores are twisted to form a cable core, and a sheath wraps the cable core. The polyimide film wraps the insulation layer, thus, the requirements of the cable for high temperature resistance and radiation resistance can be ensured. A fabrication method of the high-temperature resistant cable for the nuclear power plant comprises the steps of 1) twisting the plurality of copper or tin plated copper metal signal wires to form the conduct